Development of a Rapid and Efficient Protocol for Seed Germination and Seedling Establishment of Oryza coarctata - Lamis Berqdar; Mohamed Salem; Jian Wang; Amer Alrudayan; Muhammad Jamil; Salim Al-Babili (Bio-Protocol)
Seed germination is a critical and challenging process in the propagation of Oryza coarctata, a wild halophytic rice species. This protocol outlines the seed germination procedure for O. coarctata. All steps required for optimal germination and seedling establishment of O. coarctata in both sterile and soil-based systems are described in detail. Additionally, the protocol includes an analysis of the primary hormones, abscisic acid (ABA) and gibberellin (GA), involved in regulating seed dormancy and germination.